STRATEGI PENGEMBANGAN AGRIBISNIS KAKAO DI SULAWESI TENGAH - Siti Yuliaty Chansa Arfah (Universitas Tadulako, 2019)
In the last ten years, the performance of Indonesia’s cocoa agribusiness has been diminishing due to decreasing cacao estate area, cacao plant production and cocoa export volume. Cocoa agribusiness development strategies in Indonesia were analyzed using SWOT and Architecture Strategy, which on one hand were directed more to increase the performance of small holders cacao plantation by strengthening the role of farmer groups and optimizing the role of associations. On the other hand, the strategies for the government and private cacao estates are directed more to increase the volume of production and product diversification which are important for improving the export oriented cocoa products. Other strategies that can be implied are 1) increasing the promotional activity and 2) spreading the information about cocoa and its benefits in order to increase domestic cocoa consumption.Keywords : Cocoa Agribusiness and Road Map.